2010
DOI: 10.1089/neu.2010.1370
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Theta Dysfunction after Lateral Fluid Percussion Injury

Abstract: Chronic memory deficits are a major cause of morbidity following traumatic brain injury (TBI). In the rat, the hippocampal theta rhythm is a well-studied correlate of memory function. This study sought to investigate disturbances in hippocampal theta rhythm following lateral fluid percussion injury in the rat. A total of 13 control rats and 12 TBI rats were used. Electrodes were implanted in bilateral hippocampi and an electroencephalogram (EEG) was recorded while the rats explored a new environment, and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 54 publications
6
59
0
Order By: Relevance
“…19 Using this approach, we first attempted to recapitulate the previous result that theta power in the rodent hippocampus is reduced post-LFPI. 10,11 In Figure 1C, the power spectrum averaged across recording epochs is shown for each animal in both the sham (Fig. 1C, left-most panel) and TBI condition (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Using this approach, we first attempted to recapitulate the previous result that theta power in the rodent hippocampus is reduced post-LFPI. 10,11 In Figure 1C, the power spectrum averaged across recording epochs is shown for each animal in both the sham (Fig. 1C, left-most panel) and TBI condition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that theta power is significantly decreased in TBI relative to the sham control ( p < 0.05; t-test), consistent with previous work. 10,11 We next repeated the comparison of power values in the TBI and sham condition for all frequency bands. Figure 1C (right-most panel) shows the t-statistics comparing power for all frequencies from this comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the hippocampus, θ oscillations are known to facilitate memory processes, although the exact mechanisms are not completely understood. TBI can result in a decrease in power in the θ frequency band (39,40). However, changes in θ frequency after TBI are dependent on the severity of the injury (41).…”
Section: Methodsmentioning
confidence: 99%
“…The primary event is brief and triggers secondary processes, many of which remain active for hours to days, and contribute to a number of brain pathologies, including neurovascular dysfunction, tissue loss, and neurocognitive impairments (Floyd and Lyeth, 2007;Giri et al, 2000;Hicks et al, 2010;Meaney and Smith, 2011;Ray et al, 2002;Smith et al, 2010;Stoica and Faden, 2010;Werner and Engelhard, 2007;Yakovlev and Faden, 2001). A number of molecular mechanisms that underlie these secondary processes have been identified in rodent models and clinical studies, and represent potential targets for therapeutic intervention (Beauchamp et al, 2008;Fedor et al, 2010;Hayes et al, 2009;Huh and Raghupathi, 2009;Ottens et al, 2010;Saatman et al, 2010;Shellington et al, 2011;Sullivan et al, 2011). These include oxidative damage resulting from increased production of reactive oxygen species (ROS) and reduced glutathione levels, inflammation resulting from local and infiltrating cells, mitochondrial dysfunction, and activation of apoptotic cell death cascades (Babikian et al, 2010;Fan et al, 2003;Hall et al, 2010;Hayes and Dixon, 1994;Igarashi et al, 2001;Kelley et al, 2007;Lifshitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%